Combined platelet-rich plasma and cold water immersion treatment minimize the damage following a skeletal muscle stretch injury in rats. (16th November 2020) - Pereira Martins, Rodrigo; Hartmann, Diane Duarte; Furtado, Andrezza Bond Vieira; Luccas Duarte, Bárbara Santos; Signori, Luis Ulisses; Antunes Soares, Felix Alexandre; Pereira, Maria Ester; Puntel, Gustavo Orione
Abstract: The skeletal muscle stretch injuries are commonly observed in sports. In order to stimulate tissue healing, the platelet-rich plasma (PRP) and cold water immersion (CWI) are widely used in clinical practice. This study investigated the effects of isolated or combined PRP and/or CWI on the oxidative damage determined by a stretch injury induced in gastrocnemius muscle of rats. PRP and CWI are applied immediately after the injury, and the biochemical analysis was performed after 1, 3, 5, or 7 days. The levels of o thiobarbituric acid reactive substances and oxidized dichlorofluorescein were significantly increased, both in skeletal muscle tissue and erythrocytes preparations, and the combined PRP and CWI minimized these parameters. Moreover, combined PRP and CWI were more effective than the isolated treatments to increase catalase activity, also the ratio of reduced/oxidized glutathione, and the non-protein thiols (-SH) group levels. In conclusion, we could infer that the combination of these regular treatments used in an isolated form shows a great potential for treatments of muscular injuries.